Carbon opportunity costs of biofuels in Germany—An extended perspective on the greenhouse gas balance including foregone carbon storage - Fehrenbach, Horst; Bürck, Silvana (Frontiers in Climate, 2022)
Biomass-based fuels are frequently considered a Greenhouse Gas (GHG) emission reduction option. However, the aspect of foregone emission reduction which is related to alternative options such as renaturation is neglected in most cases. This study outlines carbon opportunity costs (COC) for biomass-based biofuels used in Germany. In 2020, raw materials for 44 peta joules of biofuels were cultivated on arable land in Germany. The area required for this amounts to 0.461 million hectares, after deducting the area for co-products such as rapeseed meal. A large part of the biofuels used in Germany is imported and occupies extensive areas, particularly in Asia, mainly through the cultivation of oil palms. In total, the biofuels consumed in Germany occupy 1.23 million hectares worldwide, which corresponds to more than 10 % of Germany's arable land. According to official data, the greenhouse gas emissions saved by using biofuels based on biomass instead of fossil fuels amounted to 9.2 million t CO2 -eq. in 2020. If this saving were renounced and instead natural vegetation were allowed to grow on the land occupied for biofuels, an average annual carbon sequestration of over 16 million t CO2 would be possible as a result. These are the COC of biofuel production, and they are significantly higher than the emission reductions from replacing fossil fuels.